1997
DOI: 10.1038/nbt0297-167
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the efficiency of cationic liposome-mediated intravenous gene delivery

Abstract: We have characterized the relationships between the design of cationic liposomes as a gene transfer vehicle, their resulting biodistribution and processing in animals, and the level and sites of gene expression they produce. By redesigning conventional cationic liposomes, incorporating cholesterol (chol) as the neutral lipid and preparing them as multilamellar vesicles (MLV), we increased the efficiency of cationic liposome:DNA complex (CLDC)-mediated gene delivery. Expression of the luciferase gene increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
248
1
1

Year Published

1998
1998
2002
2002

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 398 publications
(267 citation statements)
references
References 38 publications
17
248
1
1
Order By: Relevance
“…39 After intravenous administration of lipoplex, the lung shows the highest amount of gene expression among various organs and the lung endothelial cells are the main contributor to transgene expression. [1][2][3] We and others have confirmed that the gene expression level in the lung is 1000-10 000 times higher than that in the liver and spleen (data not shown). [1][2][3] Therefore, intravenous administration of lipoplex may be a promising gene delivery method to treat pulmonary diseases.…”
Section: Figure 3 Proinflammatory Cytokines In the Cytoplasmic Fractisupporting
confidence: 54%
See 1 more Smart Citation
“…39 After intravenous administration of lipoplex, the lung shows the highest amount of gene expression among various organs and the lung endothelial cells are the main contributor to transgene expression. [1][2][3] We and others have confirmed that the gene expression level in the lung is 1000-10 000 times higher than that in the liver and spleen (data not shown). [1][2][3] Therefore, intravenous administration of lipoplex may be a promising gene delivery method to treat pulmonary diseases.…”
Section: Figure 3 Proinflammatory Cytokines In the Cytoplasmic Fractisupporting
confidence: 54%
“…[1][2][3] Therefore, increasing attention has focused on the development of efficient in vivo gene delivery systems. However, intravenous administration of cationic lipid vectors containing plasmid DNA has been shown to initiate potent cytokine responses.…”
mentioning
confidence: 99%
“…Possible explanations that may account for the rapid decline in expression observed here and in other studies include: (1) loss of plasmid DNA and/or RNA from the transfected cells; (2) down-regulation of the CMV promoter; or (3) loss of transfected cells due to necrosis. Previous studies 21,22 reported that MLV will improve gene delivery over LUV using various cationic liposome formulations in vitro and in vivo. Our study also showed a better performance of MLV in vivo following i.v.…”
Section: Activity) Expression In All Lobes Of the Right Lung (R1-r4)mentioning
confidence: 98%
“…The discovery of new lipids, 12 the substitution of the helper lipid, cholesterol, for DOPE, 13 and steric stabilization with polyethylene glycol 14 have enhanced in vivo transfection efficiency of liposomes. The addition of polyl-lysine or protamine to cationic liposome carriers has also markedly enhanced the transfection efficiency of liposomes.…”
Section: Introductionmentioning
confidence: 99%